Accelerometer measurement for MFB evaluation in multi-cylinder diesel engine. (15th August 2017) - Chiatti, Giancarlo; Chiavola, Ornella; Recco, Erasmo; Magno, Agnese; Mancaruso, Ezio; Vaglieco, Bianca M.
Abstract: Indirect methods have great potential for engine diagnosis. Several methodologies have been proposed in the past in which indirect measurements are used for combustion sensing. This paper presents the results of the application of a methodology developed by the authors in which an accelerometer mounted on the engine block is used to characterize the combustion development in a multi-cylinder common rail diesel engine. The high correlation between accelerometer and in-cylinder pressure data allowed to use the vibration signals to evaluate the angular positions where: the combustion starts, 50% of fuel is burned over an engine cycle (MFB50) and the combustion process ends (MFB95) in two of the engine cylinders. The great accuracy of the predictions (the square value of the correlation coefficient was always higher than 0, 97) demonstrated that a single accelerometer can be used in control algorithms for the optimal positioning of the combustion process in more than one cylinder. Highlights: An accelerometer was mounted on the block of a multi-cylinder CR diesel engine. Its signal was used to obtain information on the combustion in two of the cylinders. In the vibration trace, the contribution related to the combustion events was isolated. Very high accuracy in SOC, MFB50 and MFB95 evaluation via the vibration signal.